Pasture Quality Affects Juvenile Survival through Reduced Maternal Care in a Mountain‐Dwelling Ungulate. (29th August 2016) - Scornavacca, Davide; Lovari, Sandro; Cotza, Antonella; Bernardini, Sara; Brunetti, Claudia; Pietrocini, Venusta; Ferretti, Francesco
Abstract: Lactation exerts heavy energetic and physiological costs to mothers, whilst determining early growth and survival of offspring. To mountain ungulates, access to high‐quality forage during nursing and weaning is crucial for reproductive success. We have evaluated the effects of pasture quality on suckling behaviour and winter survival of Apennine chamois Rupicapra pyrenaica ornata kids, across three areas. Areas A‐B ('poor' areas) were characterised by a reduced availability of nutritious forage, thus a lower diet quality for female chamois and kids; Area C (a 'rich' area) included a much greater availability of nutritious forage. In poor areas, pasture quality has been reduced by climatic and plant composition changes, as well as the presence of a herbivore competitor (red deer Cervus elaphus ). In poor areas, we recorded a significantly (1) lower suckling success of chamois kids (number of suckling bouts/number of suck attempts); (2) lower frequency of suckling bouts (n. suckling bouts/kid/h); and (3) lower suckling intensity (suck duration/kid/h) in respect to the rich area. Conversely, frequencies of suckling rejections and those of suckling attempts (n. events/kid/h) were the lowest in the rich area. Winter survival of chamois kids was c . 2 times greater in the rich area (45%) than in poor areas (20–26%). In the poor areas, resource scarcity induced adult female chamois to decrease maternal cares and favour their own maintenance, ultimately affecting population dynamics through kid winter mortality.